2007
DOI: 10.1007/s12011-007-8026-2
|View full text |Cite
|
Sign up to set email alerts
|

Changed Clinical Chemistry Pattern in Blood After Removal of Dental Amalgam and other Metal Alloys Supported by Antioxidant Therapy

Abstract: This study aimed to investigate a possible connection between removal of dental amalgam restorations supported by antioxidant therapy and indicative changes of clinical chemistry parameters. A group of 24 patients, referred for complaints related to amalgam restorations, underwent a removal of their amalgams. All patients were treated with antioxidants (vitamin B-complex, vitamin C, vitamin E, and sodium selenite). An age- and sex-matched control group of 22 individuals was also included. The mercury (Hg) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Nowadays, it seems that multidisciplinary approach on the assessment of trace elements in human organism can reveal the risk associated with dental materials (amalgams or orthodontic appliances) [20][21][22] or in the evaluation of concentration of various trace elements in saliva [23]. Many papers described in vivo tests, but also, in vitro studies are valuable because they are performed under controlled laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, it seems that multidisciplinary approach on the assessment of trace elements in human organism can reveal the risk associated with dental materials (amalgams or orthodontic appliances) [20][21][22] or in the evaluation of concentration of various trace elements in saliva [23]. Many papers described in vivo tests, but also, in vitro studies are valuable because they are performed under controlled laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Blood is the transport medium for the nutrients and metals to and from the tissues and, therefore, provides rapid and reliable information about the trace metal metabolism in human body [12,13]. Numerous studies have been reported in the recent years regarding the trace metal evaluation in the body liquids but because of natural significance and ease of sampling, blood is the most commonly used specimen [14][15][16].…”
mentioning
confidence: 99%
“…Studies have been performed to investigate the possible connection between changes in clinical chemistry patterns in blood after the removal of dental amalgams [73] or changes of trace elements in erythrocytes/plasma, also after amalgams/other metal alloy removal [74]. Other studies concerning caries susceptibility with the relation to trace metal concentration in saliva of primary school children have been performed [75].…”
Section: Discussionmentioning
confidence: 99%